Suicides around Major Public Holidays in South Korea. Issue 2 (23rd July 2016) - Sohn, Kitae
Abstract : A dip and peak pattern of suicide around major public holidays has been found in developed countries and explained by the broken promise effect. Focusing on two major holidays in South Korea (New Year's Day and Thanksgiving Day, both on the lunar calendar), replication of the dip and peak pattern was done by analyzing individual information on all suicides from 1997 to 2014. The replicated pattern revealed the most vulnerable group to be married men aged 50+ in nonmetropolitan areas in 2006–2014. Families, friends, and policy makers can use these findings to save the vulnerable.